2005
DOI: 10.3736/jcim20050610
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Salvia miltiorrhiza on rats with streptozotocin diabetes and its mechanism

Abstract: A19 fusion protein was highly expressed. The specific anti-A19 antiserum was prepared successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Indeed, our study showed that SM decreased urine protein excretion by 65% in STZinduced DN, which was similar to the anti-proteinuric effects of angiotensin-converting enzyme inhibitors (ACEi) or angiotensin II receptor blockers (ARB) observed in previous reports (Allard et al, 2007;Zhang et al, 2007). Consistent with a previous report, SM did not influence blood glucose levels (Liu et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, our study showed that SM decreased urine protein excretion by 65% in STZinduced DN, which was similar to the anti-proteinuric effects of angiotensin-converting enzyme inhibitors (ACEi) or angiotensin II receptor blockers (ARB) observed in previous reports (Allard et al, 2007;Zhang et al, 2007). Consistent with a previous report, SM did not influence blood glucose levels (Liu et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Tanshinone IIA, found in the rhizome of SM, also ameliorates blood pressure via eNOS stimulation in renovascular hypertension model hamsters and has renoprotective effects against the progression of DN (Kim et al, 2007(Kim et al, , 2009). Moreover, a study by Liu et al showed that SM may also have therapeutic effect in the treatment of diabetic nephropathy by suppressing the over-expressions of TGF-␤1, connective tissue growth factor, fibronectin and plasminogen activator inhibitor-1 in the renal cortex (Liu et al, 2005). However, there is no study about action mechanism focused on glucose metabolism together with inflammation in DN model induced by SM.…”
Section: Introductionmentioning
confidence: 96%
“…In our study the albumin excretion rate and creatinine clearance were markedly increased in the diabetic control [22]. We showed here that losartan and captopril reduced the increase in the urinary albumin excretion level, but did not affect creatinine clearance.…”
Section: Discussionsupporting
confidence: 50%
“…In the last mentioned study, the improvement was more significant in the Danshen treated than the Western medicine treated patients [102]. Danshen can protect rats with streptozotocin diabetes from diabetic nephropathy by suppressing the overexpressions of transforming growth factor-β 1 , connective tissue growth factor, plasminogen activator inhibitor-1 and fibronectin in renal cortex [103].…”
Section: Diabetesmentioning
confidence: 99%